Application of Diversion to Children in Narcotics Crimes - Agustinaa, Riska; Alhadi, Muhammad Nurcholis; Muslim, Ikhwanul (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The criminal justice system that has been in place so far, punishment for children involved is not criminal and does not create justice, both for the perpetrator (child) and also the victim.Purposes of the Research: Explain the implementation of diversion as a method of resolving cases of diversion applications for children involved in legal cases related to drugs.Methods of the Research: This study applied an empirical legal approach, and the location of the study was at the Samarinda City Resort Police. The primary and secondary data used came from interviews, surveys, and document studies. Qualitative analysis was carried out on this data.Findings of the Research: The results of the study show that the purpose of the implementation of the diversion system at the investigation stage is to realize restorative justice. This study shows that the role of the police in settling sentences using diversion in child crimes in the Samarinda City Resort Police area is very important. As part of the criminal justice system, the police try to protect the welfare and interests of children when handling cases related to the law.